Corrosion resistance of Ni-Ti alloy, SS18/8 alloy and thermoactive alloy in artificial saliva in the absence and presence of tea - Catherine Christy Antony Mary; Susai Rajendran; Jayaprahasam Jeyasundari; Rajendran Dorothy (Zaštita Materijala)
Corrosion resistance of Ni-Ti alloy, SS18/8 alloy and thermoactive alloy in artificial saliva (AS) in the absence and presence of tea has been evaluated by such as polarization study. For Ni-Ti alloy, SS18/8 alloy and thermoactive alloy, polarization study lead to the conclusion that corrosion resistance of Ni-Ti alloy and thermoactive alloy decreases in the order AS + Tea > Tea > AS Hence, people implanted with orthodontic wire, made of Ni-Ti alloy and thermoactive alloy can take tea orally without any hesitation. For SS18/8 alloy, polarization study lead to the conclusion that corrosion resistance of SS18/8 alloy decreases in the order AS > AS + Tea >Tea So, people implanted with orthodontic wire, made of SS18/8 alloy should avoid taking tea.